SUBJECT COMPOSITION OF PARTICIPANTS IN LEGAL RELATIONS RELATED TO THE PROTECTION OF INTELLECTUAL PROPERTY IN EDUCATIONAL INSTITUTIONS - Valeria B. Zolotova (Russian Studies in Law and Politics)
Purpose. The purpose of the presented work is the study and analysis of the subject composition of participants in legal relations related to the protection of intellectual property in educational institutions, the identification of their rights and obligations, as well as the definition of mechanisms for the protection of intellectual rights in the educational environment. At the same time, it is taken into account that trends in the commercialization of educational materials and to increase their marketability in the market cause a significant expansion of the subject composition, in particular, educational platforms are expanding, specialized organizations engaged in relevant activities appear, as well as specialists engaged in the preparation of educational and educational material.